Mirror Mode Storms Observed by Solar Orbiter. Issue 11 (27th October 2022) - Dimmock, A. P.; Yordanova, E.; Graham, D. B.; Khotyaintsev, Yu. V.; Blanco‐Cano, X.; Kajdič, P.; Karlsson, T.; Fedorov, A.; Owen, C. J.; Werner, E. A. L. E.; Johlander, A.
Abstract: Mirror modes (MMs) are ubiquitous in space plasma and grow from pressure anisotropy. Together with other instabilities, they play a fundamental role in constraining the free energy contained in the plasma. This study focuses on MMs observed in the solar wind by Solar Orbiter (SolO) for heliocentric distances between 0.5 and 1 AU. Typically, MMs have timescales from several to tens of seconds and are considered quasi‐MHD structures. In the solar wind, they also generally appear as isolated structures. However, in certain conditions, prolonged and bursty trains of higher frequency MMs are measured, which have been labeled previously as MM storms. At present, only a handful of existing studies have focused on MM storms, meaning that many open questions remain. In this study, SolO has been used to investigate several key aspects of MM storms: their dependence on heliocentric distance, association with local plasma properties, temporal/spatial scale, amplitude, and connections with larger‐scale solar wind transients. The main results are that MM storms often approach local ion scales and can no longer be treated as quasi‐magnetohydrodynamic, thus breaking the commonly used long‐wavelength assumption. They are typically observed close to current sheets and downstream of interplanetary shocks. The events were observed during slow solar wind speeds and there was a tendency for higher occurrence closer to the Sun. The occurrence is low, so they do not play a fundamental role in regulating ambient solar wind but may play a larger role inside transients. Plain Language Summary: Plasma strives to be in equilibrium with little to no free energy. However, this is often not the case, especially in close proximity to complex structures such as shock waves and interplanetary coronal mass ejections (ICMEs). The latter is an eruption of plasma from the Sun that propagates outward into the solar system. In the presence of some free energy, instabilities will arise to remove it, one example is the mirror mode (MM) instability. Instabilities such as these are of extremely high importance to plasma physics as they act as a feedback mechanism to the plasma. Nevertheless, there are many open questions regarding the MM instability, especially when their properties are different from the most common scenarios. Typically, MMs in the solar wind appear as dips that are isolated structures. However, this paper investigates MMs when they appear as sudden bursts of magnetic peaks and dips and typically have smaller temporal scales. These kinds of MMs have been called MM storms. This study aims to address at what distances from the Sun they arise, what types of solar wind structures they are associated with, quantify their physical properties, and understand what local plasma conditions are important. Key Points: Mirror mode (MM) storms predominantly occurred during slow solar wind Heliospheric plasma sheet crossings were effective at setting up MM unstable conditions Spatial scales of MM structures approached and were smaller than ion‐scales